Role of routine computed tomography in paediatric pleural empyema. Issue 10 (20th May 2008) - Jaffe, A; Calder, A D; Owens, C M; Stanojevic, S; Sonnappa, S
Abstract : Background: The incidence of empyema in children is increasing worldwide. While there are emerging data for the best treatment options, there is little evidence to support the imaging modalities used to guide treatment, particularly with regard to the role of routine CT scanning. The aims of this study were to develop a radiological scoring system for paediatric empyema and to assess the utility of routine CT scanning in this disease. Methods: Children with empyema were prospectively enrolled over a 3-year period into a randomised clinical trial of video-assisted thoracoscopic surgery versus percutaneous chest drain insertion and urokinase. All children received a preoperative chest radiograph (CXR), pleural ultrasound scan (USS) and chest CT scan. In the urokinase arm the clinician inserted the drain with USS evidence only and did not have access to the CT scan at the time of insertion to reflect clinical practice. A scoring system was developed for each individual radiological modality and used to compare imaging characteristics of the pleural fluid collection and underlying parenchyma and to assess the utility of USS and CT to predict length of stay after the intervention. Results: Of the 60 subjects recruited, 46 had USS images available for review, 36 had a CT scan which met the inclusion criteria and 31 had all three radiological measurements (CT, USS and CXR) available for analysis. There was substantial interobserver agreement for USS grades (κ = 0.709) and moderate agreement for total CT scores (κ = 0.520). There were weak correlations between USS grade and total CT score as well as CT loculation and density scores. Of the 25 CXRs showing simple opacification of the underlying parenchyma only, CT demonstrated simple consolidation (n = 14), necrotising pneumonia (n = 7), cavitary necrosis (n = 3) and pneumatoceles (n = 1). No abnormality was detected on CT scanning which directly altered clinical management. Neither the USS score nor the CT score, nor a combination of the two, were able to predict length of hospital stay. Conclusions: CT scanning detects more parenchymal abnormalities than chest radiography. However, the additional information does not alter management and is unable to predict clinical outcome. This suggests that there is no role for the routine use of CT scanning in children if treated with urokinase and percutaneous chest drain. The omission of routine CT scanning in empyema will reduce the exposure of children to unnecessary radiation and reduce costs. Trial registration number: The trial is fully registered with clinicaltrials.gov (ID: NCT00144950).